Cape Elegance Sdn. Bhd. ("CESB") a Case Study - Ismail, Rahmat (1997)

(untitled)
It was a monthly affair at BI Walden Management Sdn. Bhd. ("BIW") to hold an Investment Committee Meeting (LCM). The personnel who participa ted in ICM were mainly the approving authorities such as Lip-Bu Tan (Managing Director for Walden International Investment Group), CC Tang (Managing Director for Walden Singapore), KK Kuah (Executive Vice President for Walden Malaysia), and other Investment Officers; i.e. Norazharuddin Abu Talib (Assistant Vice President), Chang Tat Cyan (Financial Controller), and Ismail (Investment Analyst).